Citizenship in a post-colonial context : comparing Portugal and the Netherlands - Jerónimo, Patrícia (2011)
This paper analyses citizenship and migration regimes in a postcolonial context and presents a focused comparison of the experiences in Portugal and the Netherlands. While colonial regimes in both cases were largely exclusionary, and only towards the end of the regimes hesitantly extended citizenship to the native population, the postcolonial experiences display significant differences. While Portugal is more nostalgic about the colonial affair, cherishing the idea of cultural ties within a Lusophone community, the change was more abrupt in the Netherlands, after an initial transition period. The comparison in this paper highlights how these two countries dealt with the loss of empire.